Tempat Sampah EmAs Untuk Mendukung Wisata Kuliner MeWah Yang Berkelanjutan - Fahrul Arrozi; Muhammad Zidan Azzaki; Ummi Hani; J. Juniarti; Hartian Indriani; Hemalia Putri; Septiani Irahmatia; Imam Daffari; I Gde Abhi Bayu Pranambhawa; I Gede Krisna Satya Nandana; Ida Ayu Oka Suwati Sideman (CV. Multi Kreasi Media, 2026)
Limited space in the MeWah culinary tourism area of ​​Tempos village, along with visitors' perceptions of natural attractions such as rice fields and mountains, has caused visitors to spread their seating area to receive culinary services up to 187.97 meters to the north and south of the focal point. These visitors sit along the rice field embankments, sidewalks, and road shoulders. This condition makes it difficult to collect waste from the culinary market activities. Based on this, a waste collection technique is needed that uses small, lightweight equipment that is easy to move to follow the position of visitors and, if possible, uses used materials to reduce the budget of culinary entrepreneurs. In this community service activity, which uses the Community-Based Research (CBR) method, used wall paint buckets were chosen as the material, so that this product is introduced as the EmAs rubbish bin for tourists and entrepreneurs of Tempos traditional culinary market. The color chosen to cover the EmAs is green because it has a close gradation with the local natural area, and because green can reduce levels of anxiety, stress, and depression. The results of the program evaluation provided recommendations that the EmAs rubbish bins require distinctive colors and motifs to add aesthetic value.